Pendidikan Islam Berwawasan Multikultural (Manifestasi Manusia Cerdas sebagai Insan Kamil) - Siagian, Nurul; Albina, Meyniar; Lestari, Ayu; Mazid, Miftah (Cendekia Madani Nusantara, 2023)
This research aims to analyze multicultural Islamic education, the manifestation of intelligent humans as human beings. With the focus of this research, it discusses several aspects, including (1) Understanding Islamic Education (2) Goals of Islamic Education (3) Islamic Education with a Multicultural Insight (4) Ultimate Goal of Islamic Education with a Multicultural Insight, Manifestation of Intelligent Humans as Human Beings. The research method used in this research is a qualitative method of library study analysis or what is called library research. In this case, data and information collection was obtained through various books, journals and other previous research. The results of this research reveal that the concept of Islamic religious education with a multicultural perspective cannot be separated from the concept of intelligent humans and the paradigm of Islamic religious education with the concept of Al-Insan Al-Kamil, both of which have the same mission in describing the profile of a person who is faithful and devout. In Islamic education, the characteristics of intelligent humans are defined as insan kamil, namely complete humans, who have noble character and perfect morals, as humans who believe and are devoted to Allah. Insan Kamil is a description of the manifestation of humans. who are able to fulfill their duties and obligations as God's creatures as caliphs on earth, able to carry out and develop social, national and religious tasks together.